Agricultural Extension Planning Based on Risk Mitigation: The Case of Land Conversion in Indonesia - Maman, Ujang; ., Nindyantoro; Sugiarti, Yuni (International Journal of Engineering and Technology, 2019)
Â By the massive agricultural land conversion which threatened the farming sustainability, the agricultural extension planning should not merely to improve the farming innovativeness and skill of the farmer, but it should be focused comprehensively on controlling the risk of land conversion (LCR). Therefore, the research aims to identify the event of LCR, the agents of LCR, and finally to formulate the agricultural extension planning to control the agents of LCRs. The in-depth interview with the 60 of farmer groupâ€™s head in West Java, Indonesia, from June to October 2016, the research pointed out four events of LCR and seven agents of risk induced the coming of LCR, mainly in cultivation and plant maintenance phase. Based the HOR model analysis, the agricultural extension should be prioritized sequentially to implement the integrated planning of developing the skillful volunteer to work proudly in paddy-farming; high cooperation with many sides to form the opinion that rice farming is respectable; and it should highly be supported by the government program to buy the fertile farm land sold by the owners.Â